(untitled) (مجلة إحالات, 2026)
Alarm, which calls for speeding up papers and reading the linguistic reality with the right eyes in order to find solutions to contain it. the crisis. This paper comes mainly after extrapolating the linguistic situation in Africa and Algeria specifically to stand for the colonial linguistic exchange to demolish the official language, and broaden the picture between the original Language and the speakers. And standing on the same compatibility with alternative programs to the current situation in Latin America, and resorting to systems and languages in Algeria as needed. Each language preserves its identity and protects the nation from linguistic fragmentation and disruption